Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae) - Yu, Daoyuan; Ding, Yinhuan; Ma, Yitong (Zootaxa, 2017)
Molecular analysis and a detailed morphological comparison revealed that Tomocerus similis Chen & Ma was described from individuals belonging to several species from several localities. Based on both old and new material from Anhui and Jiangsu Provinces, China, T. similis is redescribed and two new species are described. The three species are morphologically similar. Tomocerus persimilis sp. nov. differs from the others by the presence of central macrochaeta on head and of several distinct distal inner teeth on unguis. Tomocerus dissimilis sp. nov. is characterised by pointed tenent hairs on anterior legs. Remarks are made on the systematics and ecology of the kinoshitai complex, and on the taxonomic value of tenent hair and its adjacent chaetae.